Pengaruh Game Online Terhadap Interaksi Sosial Remaja Kampung Cipayung (Studi Kasus Kampung Cipayung RT05/05 Kelurahan Tengah Kecamatan Cibinong Kabupaten Bogor) - Sheni Ratna Amelia; Chodidjah Makarim; Rusdi Kasman (KOLONI, 2023)
Online games are games that utilize the internet network to access them and can be played simultaneously via each user's gadget. The development of science and technology (IPTEK) is one proof of the increasingly advanced times. Meanwhile, social interaction is a relationship between one individual and another individual, one individual can influence another individual or vice versa, so there is a reciprocal relationship. This research aims to determine the influence of online games on the social interactions of teenagers in Cipayung Village (case study in Cipayung Village RT05/RW05). The method used in this research is a quantitative approach and uses a correlational method. Based on research that has been carried out, researchers found that there is a negative influence between online games on the social interactions of teenagers in Cipayung Village. This is proven by the results of the Product Moment Person correlation test with a p value of 0.079 < 0.05 Ha accepted Ho rejected. This can be concluded that the use of online games influences social interaction among teenagers in Cipayung village.